FORMULASI STRATEGI KOMUNIKASI KARANTINA PERTANIAN MENGGUNAKAN AUDIT KOMUNIKASI - Kartikawati, Endah (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2014)
In today's global trade, Quarantine Agriculture plays a strategic role to protect local agricultural products and foodsafety. As the impact of world trade agreements, where Indonesia as a member of the organization must obey the rulesof world trade, which are non-tariff policies for export and import procedures, including agricultural products. And as aresult, Indonesian agricultural products that are still in the growth and development will experience a difficult situation.Agricultural Quarantine Agency will become the spearhead for export and import procedures to anticipate the tariff-freemarket. However, with the limited government?s resources in providingquarantine services throughout the exit and entrancein all parts of Indonesia, the Indonesian community participation in quarantine become indispensable. Public awarenessprogram be the way to increase public participation in the quarantine issues. This study aimed to evaluate public awarenessprograms that being implemented by using the method of communication audits and seek suitable strategic formula for publicawareness programs in the future. This research used a descriptive method. The respondents came from the internal thathave the scope of work to communicate with the public, and from external that selected by purposive sampling method. Datawere analyzed using descriptive methods, internal analysis, external analysis, IE analysis, SWOT analysis and QSPM. Datarepresent the attitudes and perceptions of people that passing on the exit and entry NKRI?s territory (traveler), which willbe used to develop communication strategies and public awareness programs that appropriate for Agricultural QuarantineAgency in the future.